Independent component analysis and finite element modelling of the 2004–2005 ground deformation in Tenerife (Canary Islands) - Przeor, Monika; D’Auria, Luca; Pepe, Susi; Tizzani, Pietro; Barone, Andrea; Vitale, Andrea; Pérez, Nemesio M.; Castaldo, Raffaele (Frontiers in Earth Science, 2024)
Historic volcanic activity in Tenerife was concentrated within two of the island's three dorsals and on the Teide-Pico Viejo complex located inside Las Cañadas caldera. Eruptions on the island are primarily characterised by basaltic and trachybasaltic fissural eruptions. However, the Teide-Pico Viejo complex also hosted explosive and effusive phonolitic eruptions. Our study focused on the analysis of the 2004-2005 unrest in Tenerife, which was characterised by an onset of a ground deformation pattern, heightened on-land seismic activity, changes in the chemical composition of fumaroles of the Teide composite volcano, an increase in diffusive emissions of carbon dioxide along the NW rift, and, significant gravity changes. We used the Envisat-ASAR satellite images from 2003 to 2010 to generate the LOS SBAS-DInSAR deformation time series to investigate the source responsible for ground deformation. We applied the Independent Component Analysis (ICA) to separate distinct ground deformation patterns. Specifically, we selected four components for the ICA decomposition: the first one mainly affects the stratovolcano's summit region of Teide and shows a circular symmetry; the second and third components are possibly related to the topography and atmospheric artifacts, while the fourth contains only a noisy signal. We employed a non-linear optimisation approach in a Finite Element modelling environment to determine the source geometry responsible for the first identified ICA pattern of ground deformation within Las Cañadas. We used a three-axis ellipsoidal geometry for the causative source. Our results revealed that the reactivation of a horizontal magmatic body beneath the Teide volcano is the most likely source for the observed deformation between 2004 and 2005.